Didácticas activas en la enseñanza de entomología forestal para la formación integral de ingenieros forestales. - Diodato, Liliana (2026)
Forest entomology, as a key discipline in pest management, plays an important role in the training of forestry engineers. This study presents a descriptive analysis of the implementation of active teaching strategies in the instruction of this subject between 2014 and 2024. Active methodologies, such as laboratory practices, field trips, problem-solving, and project-based learning, were combined with traditional lectures. A total of 105 students completed the course during the analyzed period, with an average final grade of 8.48 on a 0-10 scale.  In addition, a survey administered to former students (response rate: 60.56 %) collected perceptions regarding learning outcomes and evaluation methods. Respondents reported high levels of satisfaction with the use of diverse teaching and assessment strategies. The experience suggests that combining active methodologies with structured lectures may contribute to the development of technical competencies, teamwork skills, and professional communication. Although the study is descriptive and does not include a comparative design, the findings highlight the potential value of diversified teaching approaches in forestry education and their possible transferability to related disciplines.